TEACHER – STUDENT COMMUNICATION FROM PARENTS’ PERSPECTIVE DURING ONLINE TEACHING IN THE TIME OF CORONA CRISIS - Maras, Andrej (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
COVID-19 virus, still relatively unknown to the general public, has taken over the world. The period of the coronavirus epidemic has affected all segments of life, including the education system. The traditional way of teaching (face to face) has been replaced by online teaching and a virtual environment through the mediation of information and communication technologies. The aim of this research is to gain insight into parents ’perceptions of teacher-student communication during online teaching in the time of corona crisis. Fifteen parents of lower primary school students participated in the research. A semi-structured interview was used for data collection purposes. Participants’ statements indicate that during online teaching students most often communicated with their teachers via e-mail, WhatsApp, Zoom, Google Classroom, and Teams. As one of the biggest advantages of communication during online teaching, participants stated the improvement of their children's digital competencies and introduction to various communication tools, while they said that the biggest disadvantage were technical difficulties. In order to improve communication between teachers and students during online classes, participants suggested that teachers use videoconferencing more often in their teaching and organize various discussions in virtual classrooms and online forums.